THE EFFECT OF ULTRAVIOLET (UV), BA, AND NAA RADIATION ON BRANCH EXTREMES TANACETUM PARTHENUIM L. PLANT GROWN OUTSIDE VIVO - Al-Musawi, Zainab J.; Muhammad, Sajid U. (Diyala Agricultural Sciences Journal, 2020)
The research was carried out in the plant tissue culture laboratory of the College of Agricultural Engineering Sciences for the period from February 2015 to August 2016, with the aim of studying the effect of UV treatment and some growth and interference organizations between them on the characteristics of vegetative growth. The experiment was carried out according to the complete random design (CRD) presented Seed to ultraviolet (UV.B) and for different periods of time 5,10,15,20 minutes, UV treatment for 15 minutes was the best and was adopted in conducting the experiment after which the plants were transplanted to MS medium equipped with different concentrations of Benzyl Adenine BA) ((0.0, 1.0, 2.0, 3.0 mg. L-1 ) interfered with Naphthalene Acetic Acid (NAA) (0.0, 0.1, 0.3, 0.5 mg. L 1- ) with 10 replicates per concentration. The dietary medium equipped with 1 mg. L - 1. of BA and 0.5 mg. L-1 . of NAA was better in increasing the number of vegetative branches and the soft and dry weight of exposed plants. UV (it recorded 7.300 branches. Plant 1., 1.996 g, 0.097 g respectively) compared to the measurement treatment for non-irradiated plants that were the lowest in achieving the increase, as it recorded 2.400 branches. Plant 1., 0.014 g and 0.010 g in succession . We conclude from the above that the treatment with ultraviolet radiation (UV) for a period of 15 minutes, treatment with different concentrations of plant growth regulators and their interaction had a significant effect on the growth characteristics of Tanacetum parthenuim L. planted tissue culture